Some aspects of the correlation of morphological changes in the vessels of the articular capsule, subchondral bone and articular cartilage in cardiovascular diseases with damage to the lower extremities - Zherebkin , V.V.; Shiyan , D.N.; Borzenkova , I.V.; Tkachenko , P.V. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. The exact pathogenetic mechanism (or mechanisms) of osteoarthritis is still unknown, despite current advances in diagnosis, which explains the preclinical and clinical failure of a number of potential disease-modifying pharmacological therapies. The need to increase the effectiveness of therapy for this common disease leads to further research into its pathogenesis. Objective. Determination of possible pathogenetic mechanisms of osteoarthritis by studying the relationship between vascular changes in the joint capsule and morphological changes in articular cartilage and subchondral bone. Methods. Histological studies of the articular tissues of 30 lower limbs amputated in persons with vascular diseases of the lower extremities without a clinical diagnosis of osteoarthritis were carried out. Results. Samples of the knee joint capsule revealed signs of arteriosclerosis with obliteration of up to 90 % of the vascular lumen and manifestations of venous thrombosis with revascularization of blood clots. At the same time, in the subchondral bone, phenomena of severe osteoporosis with sclerosis and fibrous restructuring of adipose tissue were detected, and in the articular cartilage - phenomena of dystrophy with delamination of the surface layer. Conclusion. Pathological changes in the vessels of the joint capsule and subchondral bone in the structure of cardiovascular diseases and the manifestations of dystrophic destruction of articular tissues caused by them can be considered as the leading pathogenetic mechanism of primary OA. Further studies of the correlation of morphological changes in articular tissues by comparing samples of different contingents of individuals are expedient.